A BIBLIOMETRIC ANALYSIS OF THE PUNICA GRANTUM L. LITERATURE - Al-Qallaf, Charlene L. (Malaysian Journal of Library and Information Science, 2009)
The purpose of this study was to identify and analyze the intellectual structure of the Punica granatum L (pomegranate) literature and to determine trends and patterns. Specific areas addressed were growth of the literature, publication type, author productivity and patterns, subject focus, language dispersion, and characteristics of the journal literature. Thirty-one related databases and the online catalogs of two United States national libraries were searched to identify publications. The final data set consisted of 3,306 items. All publications were reviewed through 2006. Data were sorted and manipulated using the software package ProCite. For analysis of the data, bibliometric techniques were applied. The results show that the literature has grown consistently from 1970 onwards exploding to significant proportions beginning in 2000. Most of the publications are the result of author collaboration (7l.82%) and written in the English language (69.57%). India and the United States are the leading contributors to the literature and educational institutions make-up more than fifty percent of the authors’ affiliation. The literature is multi- and inter-disciplinary in nature. The major subject areas are plant diseases, growth (plants), botanical chemistry, pharmacognosy, and plant products. Journal articles (75.53%) constitute the largest single type of publication. There are 1,045 unique journal titles containing 2,497 publications. According to Bradford’s Law a core of 38 journal titles form the nucleus of this literature. This study provides future direction for researchers, facilitates discussion within multiple disciplines, and assists information providers in formulating policy guidelines for the selection and acquisition of information resources.